The influence of Dapagliflozin on dietary mediated physiological and behavioral changes - Ryan, Shane P. P., author; Bell, Christopher, advisor; Melby, Christopher, committee member; Braun, Barry, committee member (Colorado State University. Libraries, 2019)
The diabetes medication, Dapagliflozin, is a sodium-glucose co-transporter 2 (SGLT2) inhibitor. The mechanism of action is decreasing renal absorption of glucose, leading to glucosuria, and modest weight loss. We hypothesized that SGLT2 inhibition would potentiate the favorable influence of dietary counseling on body composition and physiological adaptations in overweight or obese adults. Fifty sedentary overweight/obese men (n = 12) and women (n = 38) were randomly assigned to 12 weeks of dietary counseling for weight loss, supplemented with daily ingestion of either placebo or Dapagliflozin (up to 10 mg/day); coded as Pill A and Pill B. Dietary counseling consisted of weekly, one-on-one, 30-minute meetings targeting modest calorie restriction. Before and after treatment, body composition, resting metabolic rate (RMR), insulin sensitivity, appetite and satiety were measured. Twelve weeks of dietary counseling decreased (P < 0.049) body mass, fat mass, and RMR; neither variable was influenced by pill assignment (interaction: P > 0.264). Dietary counseling also decreased lean mass (treatment main effect: P < 0.001), however the decrease in lean mass was greater in Pill B than in Pill A (interaction: P = 0.037). Neither dietary counseling nor SGLT2 inhibition influenced insulin sensitivity (P > 0.055). Overall, 12-weeks of dietary counseling leads to favorable modification of body mass and fat mass regardless of pill assignment. However, Pill A appears to reduce the dietary counseling mediated loss in lean mass. Except for lean mass, the effects of dietary counseling for weight loss were not influenced by SGLT2 inhibition.